EAFIT Children's University Off-Campus (2011)
This year, EAFIT Children's University participated in different city events, bringing questions, activities and conversations to other spaces and other audiences. Some of these events in which we participated were the Book and Culture Festival, ST+i Fair, LabSurlab, and The City and Children, among others.